Perspectives on teaching and learning chinese literacy in China - Ruan, Jiening; Leung, Cynthia B. (Multilingual Education, 2012)
This is one of two volumes by the same editors that explore historical, philosophical, and cultural perspectives on literacy in China. This volume focuses on Chinese literacy, while the other volume is on English literacy. Since the founding of the People's Republic of China, the country has witnessed a dramatic increase in its literacy rate, but not without challenges. The essays in this volume provide a comprehensive, cross-disciplinary look at changes in Chinese literacy education from ancient times to the modern day. Together, the essays address a wide array of topics, including early Chinese literacy development, children's literature, foreign translated literature, and uses of information technology to teach Chinese. This authoritative text brings clarity and precision to the field and serves as a vital core resource for those who want to expand their understanding of Chinese literacy education. Its scope is unmatched even in academic literature in the Chinese language.